List of documents and publications in the field of mass communication (1984-1985) (UNESCO ParisFR, 1986)
Consists of 3 sections viz. a main list which provides full bibliographic description for each item. These items are classified in alphabetical order by title of document, meeting or institution. In the other two sections - the subject and author indexes provide references to headings under which items are more fully described in the main sequence.
IDS